2016
DOI: 10.1016/j.jpsychires.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle interventions targeting dietary habits and exercise in bipolar disorder: A systematic review

Abstract: Background Bipolar disorder (BD) is a serious mental illness associated with a high risk of medical comorbidities, long-term disability and premature death. This systematic review examined the current literature on therapeutic interventions targeting nutrition and physical activity in BD and collecting health-related measures such as mood and course of illness. Methods Scopus (all databases), Pubmed and Ovid Medline were systematically searched with no language or year restrictions, up to June 2015, for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 48 publications
(47 reference statements)
1
65
0
1
Order By: Relevance
“…Unhealthy lifestyle habits, such as impaired sleep, poor diet, sedentary behaviour, smoking and substance/alcohol misuse are associated with increased inflammation and impaired neuroplasticity; and are known to increase mood symptoms and cardio‐metabolic burden in mood disorders . All of these behaviours are modifiable, with growing evidence indicating that multimodal lifestyle interventions targeting exercise, nutrition and wellness are feasible and effective in improving physical and emotional health in BD . Surprisingly, the relationship between lifestyle factors and cognition has not received much research attention.…”
Section: Emerging Correlates Of Cognitive Impairment In Bdmentioning
confidence: 99%
See 1 more Smart Citation
“…Unhealthy lifestyle habits, such as impaired sleep, poor diet, sedentary behaviour, smoking and substance/alcohol misuse are associated with increased inflammation and impaired neuroplasticity; and are known to increase mood symptoms and cardio‐metabolic burden in mood disorders . All of these behaviours are modifiable, with growing evidence indicating that multimodal lifestyle interventions targeting exercise, nutrition and wellness are feasible and effective in improving physical and emotional health in BD . Surprisingly, the relationship between lifestyle factors and cognition has not received much research attention.…”
Section: Emerging Correlates Of Cognitive Impairment In Bdmentioning
confidence: 99%
“…123 All of these behaviours are modifiable, with growing evidence indicating that multimodal lifestyle interventions targeting exercise, nutrition and wellness are feasible and effective in improving physical and emotional health in BD. 124 Surprisingly, the relationship between lifestyle factors and cognition has not received much research attention.…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…It is important to obtain a detailed history of patient’s symptoms, triggers, family history and promote healthy lifestyle habits including regular exercise, adequate sleep, and proper nutrition [33]. Sedentary lifestyle is a common problem among individuals with Bipolar Disorder [34] and may consequently affect youth offspring living with a Bipolar Disorder parent.…”
Section: Resultsmentioning
confidence: 99%
“…32 Systematic reviews of interventions to increase uptake of lifestyle behaviours found some beneficial impact on CVD risk factors; however, the methodological quality of many of the included studies was low. [33][34][35] Most studies target single-risk factors and do not seek to address the full CVD risk profile of patients with SMI. Only one trial was found that tested a life goals collaborative care intervention involving management strategies for mental health symptoms and CVD risk factors.…”
Section: Cardiovascular Disease Risk Prediction Tools For People Withmentioning
confidence: 99%